An optical method for the determination of platelet count in platelet samples contaminated with red blood cells. - Lee, V; Tarassenko, L (1992)
We present a simple photometric method to determine the total concentration of platelets present in a sample independently of red blood cell concentration. Standard optical density curves for platelet samples ranging in concentration from 0 to 1.5 x 10(9) cells/ml and contaminated with red blood cells ranging in concentration from 0 to 0.03 x 10(9) cells/ml are determined. A study of the absorbance spectra of red blood cells and platelets suggests that by calculating the absorbance difference between two wavelengths, an estimate of red blood cell concentration can be made. Then, in the second step of this two-step method, the individual absorbance measurements at the two wavelengths are matched to the standard values determined previously to derive an estimate of platelet concentration. In a trial of 62 unknown platelet samples contaminated with red blood cells, the standard deviation for the error in platelet count was 0.16 x 10(9) cells/ml with a mean difference of 0.011 x 10(9) platelets/ml. We conclude that our method may be useful in laboratories not equipped with electronic cell counters as well as in applications such as the development of noninvasive measurements of platelet concentration in platelet transfusion packs.